PENINGKATAN LITERASI TEKNOLOGI MELALUI EDUKASI INSTALASI WINDOWS PADA ANAK-ANAK DI PANTI ASUHAN MUHAMMADIYAH NURUL BADRI, BEKASI BARAT - Barry Vasyah; Alfan Akbar Halim Syakur; Dita Arysanti; Fitra Listiyono; Intan Kamelasari; Muhammad Rafi Shiddiq; Nailan Shafa; Rica Rahim; Siti Ulfiah; Wendy Kautsar; Galuh Saputri (Abdi Jurnal Publikasi, 2024)
This Community Service (PKM) program aims to enhance the technological literacy of children at the Muhammadiyah Nurul Badri Orphanage in West Bekasi through Windows operating system installation education. The training aims to provide basic skills in information technology, specifically regarding computer operation and software installation. The methods used in this activity include theoretical explanations of hardware and software, as well as practical steps for Windows installation. Additionally, the activity includes interactive discussion sessions to deepen participants' understanding of the material presented. The results of this activity show an increase in participants' enthusiasm and confidence in learning technology, although no quantitative data was obtained. Several participants commented that this activity increased their motivation to learn more about computer technology. This activity is expected to contribute to improving digital literacy for children in the orphanage, as well as motivating them to develop technological skills that will be beneficial in the future. Thus, this PKM not only provides practical skills but also opens up opportunities for participants' personal development in the digital world.